Pengembangan Terapi Dingin sebagai Tindakan Mandiri Perawat dalam Mengurangi Nyeri pada Klien - Maria Putri Sari Utami (Jurnal Keperawatan Notokusumo, 2015)
Pain is the most common reason for a person to health care. Pain is subjective, so there is no pain equal to each other. If the pain is not treated, the pain will interfere with the activity, lowering ability, and affect quality of life. Pain experienced by the patient is pain physically and emotionally affect patient. Therefore we need a non farkamologi approach to overcome the pain. One of the non-pharmacological therapies are much in demand today is cold therapy. This therapy is desirable that all societies as effective, inexpensive, easy and has proven to reduce pain. The purpose of the study was to test the influence of cold application on pain. Search using keywords Ice, Cold, Cool therapy, Application as independent variables and pain as the dependent variable. Searches performed on the website Proquest, Ebscohost, PubMed, ScienceDirect and other websites that use the Google Scholar aid . From the search results obtained 6 related articles. The jounals is clinical studies with Randomized Controlled Trial (RCT). The results of the literature review found that in terms of the effectiveness of therapy, six articles mentioned that the cold therapy has the ability to reduce pain in patients.